Evaluation of the Relationship Between BDNF Val66Met Gene Polymorphism and Attention Deficit Hyperactivity Disorder: A Meta-Analysis - Mei, Shufang; Chen, Wencai; Chen, Sijing; Hu, Yani; Dai, Xiaoyan; Liu, Xiujun (Frontiers in Psychiatry, 2022)
Background: Attention deficit hyperactivity disorder (ADHD) is a common neurobehavioral disorder in childhood. Brain-derived neurotrophic factor (BDNF) is widely distributed in the central nervous system and plays an important role in neural development. Despite several previous studies have examined the association between the Val66Met polymorphism BDNF and ADHD, the results are conflicting. Objective: This study aimed to evaluate the association between Val66Met polymorphism and ADHD in case-control and TDT studies using a meta-analysis. Methods: Keywords “rs6265” or “Val66Met” and “Attention deficit hyperactivity disorder” were used to search in the PubMed, Embase, Web of Science, Wanfang, and China National Knowledge Infrastructure databases before April 2021. Genotype data were extracted to calculate odds ratios (ORs) and 95% confidence intervals (CIs). Results: Fifteen studies, comprising of 8,692 samples (containing 4,364 cases, 4,328 controls) and 1,578 families were included and results demonstrated that rs6265 was not associated with susceptibility to ADHD (OR = 0.95, 95% CI: 0.87–1.04, P = 0.291). Stratified analyses by study design, ethnicity, and sample size further supported that rs6265 was not associated with ADHD. Conclusions: The present study shows that the polymorphism of the BDNF Val66Met gene is not associated with susceptibility to ADHD.